AMP-Activated Protein Kinase (AMPK): Regulation of Metabolic Gene Expression - Varanasi, U. S. (Current Medicinal Chemistry - Immunology, Endocrine & Metabolic Agents, 2005)
AMPK (AMP-activated protein kinase) is a serine/threonine kinase that functions as a metabolic master switch by regulating ATP consuming anabolic pathways and ATP generating catabolic pathways in response to cellular energy status. It is activated in response to stresses such as: diabetes, hypoxia, toxins, nutrient deprivation, hormones and drugs. Although most of the known functions of AMPK are due to regulation of metabolic enzyme activity in cytoplasm, a growing body of evidence suggests that AMPK also functions as major regulator of metabolic gene expression. Here I review our current understanding of how AMPK regulates gene expression at the transcriptional, mRNA stability, and protein synthesis levels.
Keywords: chrebp